(3x+7)(x-7)=6x+14

Simple and best practice solution for (3x+7)(x-7)=6x+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+7)(x-7)=6x+14 equation:


Simplifying
(3x + 7)(x + -7) = 6x + 14

Reorder the terms:
(7 + 3x)(x + -7) = 6x + 14

Reorder the terms:
(7 + 3x)(-7 + x) = 6x + 14

Multiply (7 + 3x) * (-7 + x)
(7(-7 + x) + 3x * (-7 + x)) = 6x + 14
((-7 * 7 + x * 7) + 3x * (-7 + x)) = 6x + 14
((-49 + 7x) + 3x * (-7 + x)) = 6x + 14
(-49 + 7x + (-7 * 3x + x * 3x)) = 6x + 14
(-49 + 7x + (-21x + 3x2)) = 6x + 14

Combine like terms: 7x + -21x = -14x
(-49 + -14x + 3x2) = 6x + 14

Reorder the terms:
-49 + -14x + 3x2 = 14 + 6x

Solving
-49 + -14x + 3x2 = 14 + 6x

Solving for variable 'x'.

Reorder the terms:
-49 + -14 + -14x + -6x + 3x2 = 14 + 6x + -14 + -6x

Combine like terms: -49 + -14 = -63
-63 + -14x + -6x + 3x2 = 14 + 6x + -14 + -6x

Combine like terms: -14x + -6x = -20x
-63 + -20x + 3x2 = 14 + 6x + -14 + -6x

Reorder the terms:
-63 + -20x + 3x2 = 14 + -14 + 6x + -6x

Combine like terms: 14 + -14 = 0
-63 + -20x + 3x2 = 0 + 6x + -6x
-63 + -20x + 3x2 = 6x + -6x

Combine like terms: 6x + -6x = 0
-63 + -20x + 3x2 = 0

Factor a trinomial.
(-7 + -3x)(9 + -1x) = 0

Subproblem 1

Set the factor '(-7 + -3x)' equal to zero and attempt to solve: Simplifying -7 + -3x = 0 Solving -7 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -3x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -3x = 0 + 7 -3x = 0 + 7 Combine like terms: 0 + 7 = 7 -3x = 7 Divide each side by '-3'. x = -2.333333333 Simplifying x = -2.333333333

Subproblem 2

Set the factor '(9 + -1x)' equal to zero and attempt to solve: Simplifying 9 + -1x = 0 Solving 9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 0 + -9 -1x = 0 + -9 Combine like terms: 0 + -9 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9

Solution

x = {-2.333333333, 9}

See similar equations:

| 7-4x=49+3x | | -11.6+8+8.3=x | | 5p-2=13 | | 6+10+2=210 | | 25-4x=55 | | 2+3y=17 | | -4w+2(w-7)=-16 | | x^2=3z+18 | | 2(X^2)+X=.44 | | 2x-4y+3=19 | | .5x+5=8.5 | | 6x8/15 | | 4/w=-8 | | x^4+3x^3-9x^2-23x-12=0 | | y=x^4+3x^3-9x^2-23x-12 | | 1/2a+1/4b-1/4a+3/4b | | qd=1600-50p | | 3t/10=6 | | (y^7)/(y+2)*(8y+16)/(y^9) | | q=100+5p | | m^4-38m^2+72= | | q=20+p | | x+9+x+12+x-3=180 | | x^2+2=12 | | -17-5x=2x+10 | | x+20+2x-11+90=180 | | 8x-(4x+4)=16 | | Log(x+12)-logx=1 | | x+13+2x+2x-8=180 | | X=9y+3 | | 2x+6y=96 | | y=6x^5+12x^3+6x^2-6x^3+7 |

Equations solver categories